GEOGRAPHIC TONGUE PREVALENCE AND NUTRITIONAL STATUS AMONG FIRST GRADE SCHOOL CHILDREN AT TANJUNGSARI SUBDISTRICT OF SUMEDANG - Nita Septiani; Indah Suasani Wahyuni; Risti Saptarini; Nanan Nur’aeny (Dentino : Jurnal Kedokteran Gigi, 2019)
Background: Geographic tongue (GT) is a state of the tongue surface which is characterized by an atrophic filiform papillary, a rising in surrounding borderline with yellowish white appearance, and presentations in varying locations and shapes. One of the predicting factors of GT is nutritional deficiency. Objective: to determine the prevalence of GT and nutritional status among first grade school children at Tanjungsari Subdistrict of Sumedang. Methods: It was a descriptive research with the implementation of survey method. The sampling was obtained according to inclusion criteria. The research locations comprised of three elementary school representatives in Tanjungsari sub-district, Sumedang. Nutritional status was assessed using Food Frequency Questionaire (FFQ) Results: There were 200 children with a prevalence of geographic tongue in a total of 4.5%. Nutritional status obtained a result of 11.11% student included in the above-normal criteria, 22.22% students included in normal criteria, 11.11% student included in low deficiency criteria, 33.33% students included in moderate deficiency criteria, and 22.22% students included in  high deficiency criteria. Conclusion: The prevalence of geographic tongue among first grade school children at Tanjungsari District of Sumedang is 4.5% with the highest nutritional status in moderate deficiency category.Background: Geographic tongue (GT) is a state of the tongue surface which is characterized by an atrophic filiform papillary, a rising in surrounding borderline with yellowish white appearance, and presentations in varying locations and shapes. One of the predicting factors ofGT is nutritional deficiency. Objective: to determine the prevalence of GT and nutritional status among first grade school childrenat Tanjungsari Subdistrict of Sumedang.Methods:It was a descriptive research with the implementation of survey method. The sampling was obtained according to inclusion criteria.The research locations comprised of three elementary school representatives in Tanjungsari sub-district, Sumedang. Nutritional status was assessedusing Food Frequency Questionaire (FFQ)Results: There were 200 children with a prevalence of geographic tongue in a total of 4.5%. Nutritional status obtained a result of 11.11% student included in the above-normal criteria, 22.22% studentsincluded in normal criteria, 11.11% student included in low deficiency criteria, 33.33% students includedin moderate deficiency criteria, and 22.22% students included in  high deficiency criteria. Conclusion: The prevalence of geographic tongue among first grade school children at Tanjungsari District of Sumedang is 4.5% with the highest nutritional status in moderate deficiency category. Keyword:Children, elementary school, first grade, geographic tongue; nutritional status